Role of cytomegalovirus in glioblastoma development: promoter or culprit? - Xiaoxin Wu; Zhengyu Zhang; Liang Zhang; David J Daniels (Virology Journal)
Abstract Glioblastoma is the most common primary malignant tumor of the central nervous system, with a median survival of less than two years. While the etiology of glioblastoma is unclear, viral infection has emerged as a potential contributing factor. Cytomegalovirus (CMV) was first reported to be associated with glioblastoma in 2002. Since then, many studies have detected CMV in glioblastoma tissues suggesting it may plays a role in the glioblastoma progression. While there is no direct evidence confirmings CMV as an oncogenic virus, studies have demonstrated that CMV promotes glioblastoma development in cell and animal models, with several CMV-related genes implicated in tumorigenesis. Importantly, adjuvant CMV antiviral therapy has been proven to improve glioblastoma patient survival. This review focuses on clinical studies regarding the relationship between CMV and glioblastoma, the mechanism of CMV in tumorigenesis, advances in animal models of CMV-induced glioblastoma, and key directions for future investigations.